2006
DOI: 10.1093/hmg/ddi469
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the human interleukin-1B gene affect transcription according to haplotype context

Abstract: We questioned the significance of haplotype structure in gene regulation by testing whether individual single nucleotide polymorphisms (SNPs) within a gene promoter region [interleukin-1-beta (IL1B)] might affect promoter function and, if so, whether function was dependent on haplotype context. We sequenced genomic DNA from 25 individuals of diverse ethnicity, focusing on exons and upstream flanking regions of genes of the cluster. We identified four IL1B promoter region SNPs that were active in transient tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
249
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(281 citation statements)
references
References 61 publications
16
249
2
14
Order By: Relevance
“…The haplotypes of the four polymorphisms account for more than 98% of the estimated haplotypes in Caucasians and African-Americans (Chen et al, 2006). We have previously reported that the polymorphism IL1B T-31C was associated with risk of MM (Vangsted et al, 2009) and we now extend those findings to the other known functional IL1B polymorphisms.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The haplotypes of the four polymorphisms account for more than 98% of the estimated haplotypes in Caucasians and African-Americans (Chen et al, 2006). We have previously reported that the polymorphism IL1B T-31C was associated with risk of MM (Vangsted et al, 2009) and we now extend those findings to the other known functional IL1B polymorphisms.…”
Section: Discussionsupporting
confidence: 66%
“…In a reporter gene assay-based analysis of functional effects of the individual polymorphisms using a human monocytic cell line THP-1, the polymorphism C-3737T had no major effect on transcription, but the polymorphism was shown to destroy a binding site for the NF-jB subunit p50. In a similar reporter gene-based analysis of haplotypes, a lowered promoter activity was found for the TGT haplotype after stimulation with lipopolysaccaride compared to the CGC haplotype, which had the highest response (Chen et al, 2006). Our results therefore indicate that a genetically determined low IL1B expression is associated with lowered risk of MM.…”
Section: Controlssupporting
confidence: 68%
See 1 more Smart Citation
“…The study showed that although the variant C-allele of T-31C has less transcriptional activity when analyzed separately, the haplotype encompassing both variant alleles in positions À31 and À511 has a higher transcriptional response to LPS and phorbol 12-myristate 13-acetate (PMA) stimulation in the human monocytic cell line than the haplotype encompassing the wild-type alleles. 22 This result is supported by a recent study on lung epithelial cells that found that the variant allele in position À31 had a lowered transcription level when analyzed separately. 23 We observed increased survival among patients with a higher inborn IL-1b transcription level and cytokine level.…”
Section: Discussionmentioning
confidence: 63%
“…The C allele of the promoter polymorphism IL1B T-31C results in increased IL-1β secretion upon stimulation with lipopolysaccharide. 8,9 The polymorphism IL6 G-174C is also located in the promoter region of the gene. The wild type G allele is found to have a higher transcriptional level than the variant C-allele and the presence of the Callele in healthy individuals results in low IL-6 levels and low lymphocyte levels upon stimulation.…”
Section: Introductionmentioning
confidence: 99%